INDONESIAN LAW REFORM AND THE PROMOTION OF JUSTICE: AN ANALYSIS OF LAW REFORM IN THE POST-SOEHARTO PERIOD - McGuire, Hannah (Faculty of Law, Universitas Brawijaya, 2016)
This paper focused on law reform in Indonesia post-Soeharto period. It analyses whether the promotion of justice has been conducted. It aims to analyse whether the law reform during the reign of B.J. Habibie impeded on the promotion of justice. This paper takes the position that the promotion of justice was absent during Soeharto's presidency, and through an analysis of five law reforms introduced after his downfall - No. 2 of 1999 on Political Parties, No. 3 of 1999 on General Elections, No. 28 of 1999 on Corruption, Collusion and Nepotism, No. 31 of 1999 on the Eradication of Corruption and No. 39 of 1999 on Human Rights. It is argued that that the laws introduced during the Post-Soeharto era did not see to the complete promotion of justice.